The Efforts of Islamic Religious Education Teachers in Getting Used to Congregational Prayers - Irfan Maulana, Ade (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This research aims to determine the efforts of PAI teachers to get their students used to praying together, as well as to find out the supporting and inhibiting factors in getting students used to praying together at SDIT Subulussalam, Tangerang Regency. This research method uses qualitative methods. This type of research uses descriptive research. This research does not intend to test a hypothesis, but only describes what is true about symptoms or variable conditions by means of the data obtained being presented through verbal expressions that can describe the actual conditions. The data sources in this research were Islamic Religious Education teachers and several SDIT Subulussalam Tangerang Regency students from each class to determine the effect of congregational prayer on their personality. The data collection technique is by conducting observations in the form of interviews and other sources related to the research problem and then presenting it in the form of descriptive sentences. The data analysis technique in this research was carried out using non-statistical methods through data reduction steps, data presentation and drawing conclusions. This research shows that teachers try to set a good example, provide advice, and provide good discipline to students. The inhibiting factors in getting students used to praying in congregation are students' lack of understanding of the importance of congregational prayers, student behavior, lack of teachers who exercise control, and lack of follow-up supervision from the school. family environment. Paying attention to these inhibiting factors, actions taken by PAI teachers include collaborating with students' parents in getting used to congregational prayers and being more active in taking a persuasive approach to each student.